Uma análise crítica da proposta discursiva da aliança unidos pelo Brasil - Paiva, Ana Cláudia Soares de (2015)
In this work we focus over the discursive constructions of presidential candidates Eduardo Campos and Marina Silva - exposed in interviews, debates and news reports, which formed the basis for of the direct speech cut of the candidates, consolidating the corpora of our analysis, presented by the media online Folha de São Paulo, Journal of Commerce, Diário de Pernambuco, O Globo, O Estado, Carta Capital, G1 news, see and Yahoo News - t searching to analyze as it was built and what purpose a speech which propagated a pseudo juxtaposition of the parties on the composition of the alliance United by Brazil on the political scene in 2014.. The alliance States by Brazil aimed to to present themselves socially with a transformative nature of speech (demagogic), where the union of these candidates would represent a new time in Brazilian politics, appointed by such an alliance as being the New Policy and characterizing itself as a force counterhegemonic PT policy. In view of the potential for such public discourse (political discourse) in social practice, we we anchor in the Critical Discourse Analysis approach, in a more timely manner in the socio-cognitive and discursive perspective van Dijk through different works so that we could build a path that expose the linguistic-discursive and cognitive strategies used by the candidates in order to access the mental representations of voters. For this we consulted van Dijk (2000a, 2000b, 2005 and 2012), to obtain a better understanding of how the ideological representations form and determine the social functioning of individuals within the communicative situation also we reviewed Fairclough (2001), seeking in their studies comprehend how is this interface between speech and subject and how both are modified and socially modify their relations. To deepen the power and access of society in political constructions by an attempt to change the models contexts of voters, we prioritize the studies of van Dijk (2010, 2012), through the reflection of the socio-cognitive elements members of macro-structural composition of speech yet in deepen of this mocroestruturação review some authors of political philosophy and political science, represented here by Pedro Demo (1999) and Gaetano Mosca (1924) in order to to understand better the political orientation that guided discursivization of the alliance PSB-Network. To circumscribe the linguistic and cognitive and discursive strategies that guided these constructs, we analyze them in order to get clues about the possible meanings intended by such speech constructions. We identify a permanent insistence around the idea of a government program, which would represent the illusory proposal for a policy that breaks away from the elites. Finally, we demonstrate, by our analysis, there was rather a polarizing voices and power among such candidates be at PSB-Rede orientation, whether the reorientation Rede-PSB which dates back to the old way of doing politics of party agreements.